A Levinasian Ethics for education's commonplaces : between calling and inspiration - Joldersma, Clarence W.; SpringerLink (Online service). (New York : Imprint: Palgrave Pivot, 2014)
Joldersma applies Levinas's ethics systematically to the commonplaces of education - teaching, learning, curriculum, and institutions - and elucidates the role of justice and responsibility and the meaning of calling and inspiration in education.
Keywords: Science; Science; Science, general